Application Simplex Lattice Design on Optimizing Formula of Ketoprofen Matrix Patch Transdermal - Eka Indra Setyawan; Akhmad Kharis Nugroho; Achmad Fudholi (Journal of Food and Pharmaceutical Sciences, 2019)
Ketoprofen is a propionic acid derivative that has anti-inflammatory, analgesic, and antipyretic activity. Transdermal patch dosage form is the right choice for ketoprofen in an effort to minimize side effects, improving patient compliance and ensure the achievement of therapeutic targets.